Diagnostic Value of Quantitative Perfusion Computed Tomography Technique in the Assessment of Tumor Response to Sorafenib in Patients With Advanced Hepatocellular Carcinoma. Issue 2 (March 2019) - Ippolito, Davide; Querques, Giulia; Pecorelli, Anna; Talei Franzesi, Cammillo; Okolicsanyi, Stefano; Strazzabosco, Mario; Sironi, Sandro
Abstract : Aim: The aim of this study was to assess the role of dynamic contrast-enhanced perfusion computed tomography (pCT) imaging in the early detection of blood flow changes related to antiangiogenic treatment with sorafenib, in patients with advanced hepatocellular carcinoma (HCC), being the modified Response Evaluation Criteria in Solid Tumors (mRECIST) criteria the standard of reference. Methods: Between 2012 and 2016, 43 cirrhotic patients (male, n = 39; female, n = 4) with biopsy-proven multifocal HCC underwent multi–detector-row computed tomography, and pCT examinations were performed before and every 2 months after sorafenib administration. Perfusion CT technique is based on the acquisition of 16 dynamic slices/scan per 40 scans, performed on a 256-slice multi–detector-row computed tomography scanner, after intravenous bolus injection of 50 mL of iodinated contrast agent (350 mg I/mL) at a flow rate of 5 mL/s. According to mRECIST, patients were stratified into complete (CR) or partial response (PR) and stable (SD) or progressive disease (PD). The following pCT parameters were calculated: hepatic perfusion (mL/s per 100 g), time to peak (seconds), arterial perfusion (mL/s), and hepatic perfusion index (%). Perfusion CT values at baseline and first follow-up were reported for all mRECIST groups and then compared between the nonprogressor (CR, PR, SD) and progressor groups (PD). Results: Most pCT values were significantly higher ( P < 0.01) between baseline and follow-up in the CR and PR groups, whereas nonsignificant differences were found among SD patients, and a nonsignificant trend ( P > 0.05) toward increase was observed among PD patients. Moreover, pCT values were significantly higher ( P = 0.05) at baseline in the nonprogressor group compared with the progressor. Conclusion: Preliminary results suggest that pCT adds quantitative data of vascularization, thus demonstrating its usefulness in the assessment of therapeutic response to sorafenib in advanced HCC, in line with mRECIST criteria, offering 1-step information on tissue cellularity and vascularization.